الغزو المغولي لسمرقند دراسة في التحولات السياسية والعسكرية فيما وراء النهر (617 هـ / 1220 م) (Comprehensive Journal of Science, 2025)
This study examines the Mongol invasion of Samarkand in 617 AH / 1220 CE as a pivotal event in the history of Transoxiana and a significant episode in the collapse of the Khwarazmian state. The research aims to analyze the political, military, and social circumstances preceding the invasion, to trace the stages of the siege and collapse, and to evaluate the role of the Khwarazmian leadership in either mitigating or accelerating the city’s fall. It also compares Islamic and Mongol historical narratives to reveal the factual dimensions of the event and move beyond the emotional tone present in some traditional sources.The study adopts a historical-analytical approach combined with comparative source criticism, reconciling divergent accounts to identify internal and external factors contributing to the fall of Samarkand, including poor military coordination, leadership instability, and the rise of a highly organized Mongol force.The research concludes that the fall of Samarkand was not merely a result of Mongol military superiority but arose from a confluence of political, military, and social factors, highlighting the importance of critically analyzing historical sources to understand the nature and consequences of this pivotal event.